Kinetics and Mechanism of Oxidation of Reducing Sugars: A Review - Singh, J.V.; Awasthi, Anupam; Dipti; Tomar, Ashish; Singh, Devendra (Asian Journal of Chemistry, 2012)
This review summaries the kinetic and mechanistic aspects of the oxidation reaction of reducing sugars with various oxidants, with emphasis to the Cr(VI) oxidation of reducing sugars. An attempt has been made to cover the recent literature available on oxidation kinetics of reducing sugars upto June 2011.